Influence of physical activity and sports practice in the academic performance of secondary education students - Villalba Lombarte, S.; Villena Serrano, M.; Castro López, R. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
This research aims to identify whether the performance of sport and physical activity influences the academic achievement of adolescents in their school years. To do this, it has been taken through a quantitative approach to inferential character, a sample of 91 students of ESO students (n = 91). On the one hand, sport and physical activity was measured through global physical activity questionnaire GPAQ (OMS, 2004), on the other hand, have implemented a number of questions on academic performance, focusing on the overall rating the last quarter and the number of failed subjects in addition to their subjective assessment of sports. The results show that students exhibiting higher levels of physical activity have better academic performance than those not involved in the practice, both in its upper half note as the lower number of failed subjects. In turn, these results are more positive when many hours of sport are made, and students who perform also any kind of sports have a more positive assessment than physically inactive students.